Text problems - Adham Normatov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the concept of textual problems, types of textual problems, modeling of the process of solving textual problems, methods of solving textual problems, non-standard problems, logical problems, economic and statistical problems in elementary grades, a compilation of economic and statistical problems in elementary grades, and a brief description of them there is talk about teaching how to write and solve conditionals.